Ingrid Caven I am a fiction - Neyrat, Cyril 1975-; Corinne, Corinna; Marchini Camia, Giovanni; Marchini Camia, Giovanni (Fireflies Press, 2024)
From Ingrid Caven's start in cinema alongside Rainer Werner Fassbinder and the myriad extraordinary roles that followed, to her theatre performances and legendary concerts, the German actress and singer has been a force of inspiration and a vital collaborator for artists across five decades, including Werner Schroeter, Yves Saint Laurent, Jean-Jacques Schuhl, Daniel Schmid, Bertrand Bonello, Albert Serra, Claire Denis, Jean Eustache, Rita Azevedo Gomes, Raúl Ruiz and André Téchiné. On the occasion of FIDMarseille's 2024 retrospective honouring Caven, Fireflies Press is teaming up with the festival to publish Ingrid Caven: I Am a Fiction, the second title of our joint monograph series One Two Many. The book features a new in-depth interview with Caven by Cyril Neyrat and Tsveta Dobreva, a dossier of photographs and other material from her personal archive, a career-spanning essay by Erika Balsom, a conversation between Jean-Jacques Schuhl and Albert Serra, and creative texts on individual films by Philippe Azoury, Renato Berta, Bertrand Bonello, Luc Chessel, Bruce Hainley, Rachel Kushner, Nathalie Léger and Audrey Wollen."--Publisher's website
Keywords: Caven, Ingrid -- 1938-; Caven, Ingrid / Criticism and interpretation; Caven, Ingrid / Interviews; Caven, Ingrid; Actors / Germany / Biography; Acteurs / Allemagne / Biographies; Actors; Biographies; Criticism, interpretation, etc; Interviews; Germany